Effect of angled layers on failure regimes in brick-and-mortar structures - Hunter, G; Djumas, L; Brassart, L; Molotnikov, A (Elsevier, 2022)
Brick-and-Mortar structures can exhibit exceptional combinations of properties, such as high strength and toughness. The properties are highly dependent on the failure regime, namely the ability to distribute damage prior to failure. In our recent work on rectangular Brick-and-Mortar structures, we have identified a transition from localised damaged (called ‘two-peak’ failure) to distributed damage (called ‘peak-plateau-peak’ failure), depending on the brick aspect ratio and the relative normal and shear layer material properties. However, the effect of non-rectangular brick shapes on these failure regimes has not yet been explored. In this work we predict with semi-analytical modelling, and validate with experiments, that introducing an angle into the ‘shear’ layers of the Brick-and-Mortar structure to create ‘diamond’ and ‘inverse diamond’ brick shapes results in a transition from ‘two-peak’ to ‘peak-plateau-peak’ failure for low aspect ratios. It is further shown that the angle required to transition to ‘peak-plateau-peak’ failure decreases with increasing aspect ratio, and that introducing an out of-plane angled layer in the form of an osteomorphic brick shape can further decrease the angle required for the transition. Our work demonstrates that the transition from ‘two-peak’ to ‘peak-plateau-peak’ failure significantly increases the toughness of the structure, without compromising strength or stiffness, highlighting the importance of understanding and controlling the parameters that affect the failure regimes.